The big end of town : - Fleming, Grant A. (Cambridge University Press, 2004)
This book traces the evolution of large business enterprises in Australia, from the giants of the nineteenth century - such as Dalgety's, CSR and BHP - to the contemporary leaders in News Corporation and Qantas. It delves into why the market leaders became the major players, examines what was crucial to their success, and their roles in leading the Australian economy. By investigation their evolution, this book provides a useful evaluation of the factors that have led to their competitive success and provides an essential guide for all businesses in Australia and beyond